IMPROVING STUDENTS’ SPEAKING SKILL THROUGH YOU TUBE VIDEO PROJECT FOR NURSING DEPARTMENT - Risa Arroyyani (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims at discovering the effect of You Tube video project to improve students' achievement in speaking skill including pronunciation, grammatical accuracy, vocabulary, fluency, and interactive communication. It used an experimental design involving 83 Nursing students in Bantul: 44 students of Control group and 39 students of Experimental Group using simple random sampling technique. This study used statistical t-test to discover the effect of using You Tube video project in improving the students' speaking skill, particularly in English for Nursing based on the score of pretest and posttest of both groups. The t test results labeled equal variances in which t-value was 3.077, the degree of freedom (df=81), and t-table was at 1.989. The difference was significant because t-test result was higher than t table. It indicated that the achievement in the students' speaking skill through You Tube video project was improved.